Relationship between life-time noise exposure and experience of tinnitus among young adults in IIUM Kuantan - Mohd. Hashim, zirwatu Hanani; Wan Ahmad, Wan Aslynn Salwani; Lamri, Marina L. Alisaputri @ Marina (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
Introduction: Since the clinical studies have shown that people suffering from tinnitus are at a high risk of developing serious psychological disturbances or serious psychological distress (Hiller and Goebel, 1998), the purpose of this study is to determine the relationship between lifetime noise exposure and tinnitus experience among young adults in IIUM Kuantan.